Environmental Ethics - Ali, Murtaza (London, UK:. : Koros Press Limited, 2014)
Environmental ethics is a branch of applied philosophy that studies the conceptual foun- dations of environmental values as well as more concrete issues surrounding societal attitudes, actions, and policies to protect and sustain biodiversity and ecological systems. More specifically, it refers to the value that mankind places on protecting, conserving, and efficiently using resources that the earth provides. The primary aim of this book is to present a succinct account of the essential fea- tures of this subject.